LOCATION ANALYSIS ON SMART HOUSE USING PROJECTIVE TRANSFORMATION - Galih Andi Pradana; Bob Hardian; Tonny Adhi Sebastian; Hanif Rasyidi; Yulistiyan Wardhana; Gladhy Guarddin (Faculty of Computer Science - Universitas Indonesia, 2014)
In this paper, a method of location analysis for smart house is proposed. The proposed method uses projective transformation to process the input from visual sensor for determining coordinate of resident and also the entire device inside the smart house. With a good calculated coordinate, each device function in the smart house can be optimized for the good of the resident. From the experiment results, the proposed method successfully maps all coordinates of any device in the smart house up to 81% accuracy.